2009
DOI: 10.1002/jcop.20310
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' exposure to community violence: are neighborhood youth organizations protective?

Abstract: Using data from the Project on Human Development in Chicago Neighborhoods (PHDCN), we identified a significant inverse association between the variety of youth organizations available at the neighborhood level and adolescents’ exposure to community violence. We examined two non-competing explanations for this finding. First, at the individual level, we tested the hypothesis that access to a greater variety of neighborhood youth organizations predicts adolescents’ participation in organized community-based acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 52 publications
(72 reference statements)
2
63
0
2
Order By: Relevance
“…Alternatively, for male youths who tend to spend free time on the streets in unstructured, unsupervised activities, engagement in available neighborhood youth organizations should be encouraged. These organizations can provide productive outlets during non-school hours (Halpern, 2002), means to improve academic achievement, resources to promote positive self-regulation, and avenues to prevent aggressive behavior (Gardner & Brooks-Gunn, 2009). Questions surround the effectiveness of neighborhood youth organizations (after-school programs, in particular) in preventing adolescent delinquency (see Taheri & Welsh, 2014).…”
Section: Implications For Theory Research and Policymentioning
confidence: 99%
“…Alternatively, for male youths who tend to spend free time on the streets in unstructured, unsupervised activities, engagement in available neighborhood youth organizations should be encouraged. These organizations can provide productive outlets during non-school hours (Halpern, 2002), means to improve academic achievement, resources to promote positive self-regulation, and avenues to prevent aggressive behavior (Gardner & Brooks-Gunn, 2009). Questions surround the effectiveness of neighborhood youth organizations (after-school programs, in particular) in preventing adolescent delinquency (see Taheri & Welsh, 2014).…”
Section: Implications For Theory Research and Policymentioning
confidence: 99%
“…Gardner & Brooks-Gunn, 2009;Gibson et al, 2009;Kuo et al, 2000). The inclusion of these variables protects against model misspecification and confounding.…”
Section: Individual-level Control Variablesmentioning
confidence: 96%
“…The survey included ten types of exposure to community violence: seeing someone attacked with a weapon; seeing someone attacked without a weapon; having something stolen from the household; having a friend, neighbor, or family member murdered; witnessing a murder; witnessing or hearing a shooting, bombing, or riot; being in a war zone; knowing a family member or close friend who was fondled or forced to have sex; knowing a family member or close friend who was robbed or mugged; and knowing a family member or close friend who was threatened with a gun or knife. 1993; Gardner & Brooks-Gunn, 2009;Gibson et al, 2009;Richters & Martinez, 1993;Selner-O'Hagan et al, 1998; see also Buka et al, 2001). In fact, research has shown that age accounts for approximately 25% of the variation in lifetime exposure to community violence (see Selner-O'Hagan et al, 1998).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…These findings suggest that it is possible to learn through community-based organisations how neighbourhood level changes can occur. Thus, developing strong institutional theories may be informative for developing strategies to reduce structural violence, rather than recording the density of community organisations in an area, a tendency found in other studies (Gardner and Brooks-Gunn 2009;Mazerolle et al 2010).…”
Section: Future Directionsmentioning
confidence: 97%